Oncolytic viruses from the perspective of the immune system. (June 2009) - Alemany, Ramon; Cascallo, Manel
Cancer treatment with oncolytic viruses is at a crucial intersection from where two very different routes can be taken. The key role of the immune system needs to be addressed proactively to succeed. An immunocentric point of view posits that the intense immunosuppression induced by tumors can be outbalanced by the natural immunogenicity of viruses. To their advantage, viruses can be safely armed to be even more immunostimulatory. The microbe-associated inflammatory response is optimal for antigen presentation and helps to reveal the hidden tumor antigens. The induced immune effector cells patrol the organs to destroy disseminated tumor cells out of the reach of the oncolytic virus. However, as tumor immunosuppression is localized, this concept needs to be revisited because every tumor focus will have to be reached by the oncolytic virus. By contrast, virocentrics see the immune system as an obstacle to virotherapy. A virus is so immunogenic that it dominates all the elicited immunity to the detriment of a response towards tumor antigens. For them immunosuppression is the way to go, and the intense immunosuppression in and around the tumor is now an advantage, offering a privileged site for virus replication. A better oncolytic virus evades the immune system, but such a virus should be very tumor-selective to be safe. Although the trend favors immunocentrics, clinical results have been more often documented in immunocompromised patients. Trials of comparative interventions on the immune system will validate immunocentrism or virocentrism. What seems clear is that at this intersection one should take one route or the other to overcome the current limitations of virotherapy.